1990
DOI: 10.1677/joe.0.1260467
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the growth hormone receptor/binding protein in skin

Abstract: Acromegaly is characterized by coarsening of facial features, acanthosis nigricans, hypertrichosis and oily skin. To determine the site through which GH exerts these effects, we have used immunohistochemistry to localize the GH receptor/binding protein (BP) in rat, rabbit and human skin. Three monoclonal antibodies (MAb 1, 43, 263) were immunoreactive in identical locations, whereas no immunoreactivity was evident when control monoclonal antibodies (MAb 50.8 and MAb 7 (rat] were used. Skin from neonatal and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…The presence of the GH receptor in human skin and its appendages, including eccrine sweat glands, suggests a direct effect of GH (10,11), but the exact mechanism by which GH exerts its effect is unknown. However, studies using PCR have shown an abundance of IGF-I receptor mRNA in human skin biopsies (20), which could suggest an IGF-I-mediated action on skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the GH receptor in human skin and its appendages, including eccrine sweat glands, suggests a direct effect of GH (10,11), but the exact mechanism by which GH exerts its effect is unknown. However, studies using PCR have shown an abundance of IGF-I receptor mRNA in human skin biopsies (20), which could suggest an IGF-I-mediated action on skin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the effect on the skin and its appendages is in part a direct effect of GH (9). This suggestion is supported by identi®cation of the GH receptor in skin tissue, including the eccrine sweat glands (10,11).…”
Section: Introductionmentioning
confidence: 89%
“…The increased hair growth is observed in the facial and axillary regions, which may enhance masculine appearance and thereby enhance self-esteem. These effects on skin may be mediated directly at GHRs, since sweat glands in human skin and hair follicles in rat skin contain GHR immunoreactivity (Lobie et al 1990).…”
Section: Body Compositionmentioning
confidence: 99%
“…Moreover, in a study performed on athletes, we showed that the water loss recorded during exercise was positively correlated with the GH secretion rate (14). In molecular research, speci®c receptors for GH have been found in the epithelium of sweat glands (15,16).…”
Section: Introductionmentioning
confidence: 99%